Correlation of electrical and structural properties of Au contacts to KOH treated n-GaN - Moldovan, Grigore; Harrison, Ian; Roe, Martin; Brown, Paul D. (Institute of Physics Publishing, 2004)
A correlated current-voltage (I-V), electron beam induced conductivity (EBIC) and X-ray photoelectron spectroscopy (XPS) study of Au contacts to KOH treated n-type GaN is presented. A strong degradation of I-V characteristics occurs following the KOH treatment, mirrored in a reduction in the magnitude of the EBIC current, even though the EBIC images look visibly unaltered. XPS demonstrates a modification in the surfaces states, e.g. resulting in a –0.3eV shift in the binding energy of Ga3d for MBE GaN following KOH processing.